(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The research looks into the potential of generating biogas from waste generated by aquaculture. The EDF-5.4_2 bioreactor, produced by "Biotehniskais centrs" (Latvia), was utilized for the experimental study. Samples of sludge from a fish farm located in Nagļu parish, Rēzekne district were collected and analysed for their moisture and organic matter content before being mixed with crushed reeds to increase the organic matter available for fermentation and biogas extraction.In this study, biogas was produced by mixing different ratios of sludge and reed residue. The yield of biogas varied based on the temperature, with the best results being achieved at 40°C. During the experiment, 2.75 L of biogas containing 37.3% methane was produced from the mixture of 1,200 g of fish farming sludge and 100 g of crushed reeds. Although the highest methane content of 40.16% was recorded at 43°C, the total amount of biogas produced was lower by 15% at this temperature.The least favourable results were recorded at 37°C, in terms of both the amount of biogas produced and the methane content. The experimental studies demonstrate that residues from aquaculture can be used for biogas production.